2017
DOI: 10.1371/journal.pone.0187399
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between spending on electronic cigarettes, 30-day use, and disease symptoms among current adult cigarette smokers in the U.S.

Abstract: ObjectiveTo examine the relationship between spending on electronic cigarettes (e-cigarettes) and disease symptoms compared with the relationship between 30-day e-cigarette use and disease symptoms among adult cigarette smokers in the U.S.MethodsWe analyzed data from the Tobacco and Attitudes Beliefs Survey which included 533 respondents aged 24+ who were current cigarette smokers and e-cigarette ever users. Fifteen self-reported disease symptoms were included as outcome variables. Separate multivariable logis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 26 publications
0
32
0
1
Order By: Relevance
“…The PHIM assumes that the RR of dual use of IQOS and cigarettes is the midpoint of the two RRs. However, there is some evidence that dual users of cigarettes and e-cigarettes have greater risks of negative health outcomes than sole cigarette users, 18 suggesting that there could be greater risks for dual users of IQOS and cigarettes and that the PHIM model may underestimate the number of deaths attributable to dual use.…”
Section: Discussionmentioning
confidence: 99%
“…The PHIM assumes that the RR of dual use of IQOS and cigarettes is the midpoint of the two RRs. However, there is some evidence that dual users of cigarettes and e-cigarettes have greater risks of negative health outcomes than sole cigarette users, 18 suggesting that there could be greater risks for dual users of IQOS and cigarettes and that the PHIM model may underestimate the number of deaths attributable to dual use.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is critical to consider whether there is a prolonged effects of past smoking that contributes to the harm of e-cigarettes for current vapers who already quit smoking. Meanwhile, a majority of e-cigarette users also use conventional cigarettes,12 but whether dual use of e-cigarettes and cigarettes is associated with added, maintained or reduced health risk remains unknown 13…”
Section: Introductionmentioning
confidence: 99%
“…Asthma and chronic obstructive pulmonary disease are the most common causes of recurrent wheezing 14. Several studies have focused on associations of e-cigarettes use with wheezing or whistling and reported mixed results 7–9 12 15–23. One study on 2086 Southern California Children’s Health Study adolescent participants found e-cigarettes use increased risks of chronic bronchitis symptoms in teens while no significant association of e-cigarettes use with wheeze were found in teens after adjusting for cigarettes use 21.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pengeluaran rokok elektrik menjadi pengukuran paling tepat untuk mengukur intensitas penggunaan rokok elektrik (Yao et al 2017). Bahkan Yao (2017) menemukan hubungan yang positif atarara pengeluaran rokok dengan gejala sesak napas pada 533 responden yang di teliti.…”
Section: Pendahuluanunclassified